MINANGKABAU LEADERSHIP PHILOSOPHY: Synthesizing Religion, Adat, and Intellectuals in the History of Islamic Political Thought - Hakim, Lukmanul; Hadi, Rahmad Tri; Ahmad, Ahmad (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
This article explores the Minangkabau leadership philosophy through the perspective of the history of Islamic political thought, focusing on the integration of Islamic values, customary principles, and the role of intellectuals in traditional Minangkabau society. The research problem centers on how this local leadership model rooted in concepts such as Tungku Nan Tigo Sajarangan and Tali Nan Tigo Sapilin reflects the evolution and localization of Islamic political concepts, particularly concerning authority, justice, and legitimacy. Using a qualitative method and a historical-analytical approach, the study draws on classical Islamic political texts and local Minangkabau sources to trace continuities and adaptations in political thought. The findings indicate that the Minangkabau leadership tradition embodies a contextualized interpretation of Islamic political ideas that has endured across generations. It suggests that this tradition, when revisited with empirical data from relevant contemporary stakeholders, can offer practical frameworks for cultivating integrity-based and sustainable leadership in modern Muslim societies. This study contributes to broadening the discourse on Islamic political thought by emphasizing indigenous contributions and the relevance of local wisdom in contemporary governance.